Introduction - Foley, Janice R. (Unions, Equity, and the Path to Renewal, 2009)
Provides a synopsis of the volume, the impetus for which began with the 2005 workshop “Advancing the Equity Agenda Inside Unions and at the Bargaining Table,” sponsored by the Centre for Research on Work and Society at York University.
Keywords: Canada; Equality; Labor unions; Social aspects; Women in the labor movement